Pengaruh Earnings Per Share, Return On Equity, Debt Equity Ratio Terhadap Return Saham (Sudi pada Perusahaan LQ45 yang terdaftar di BEI periode 2019-2021) - Rizka Mukhlisiah; Gilang Kartika Hanum (UNIVERSITAS RAHARJA, 2023)
This study aims to examine the effect of Earnings Per Share, Return On Equity, Debt Equity Ratio on Stock Returns. The statistical method used uses multiple regression analysis. The type of data used in this research is secondary data whose data source was obtained from the Indonesia Stock Exchange for the 2019-2021 period. The population in this study were 18 companies that entered the LQ45 period 2019 -2021 on the IDX. The results of this study indicate that Earnings Per Share has an effect on Stock Returns, Return On Equity has an effect on Stock Returns, while Debt Equity Ratio has no effect on Stock Returns. But Earning Per Share, Return On Equity and Debt Equity Ratio simultaneously or jointly affect Stock Returns.